Explaining the species richness of birds along a subtropical elevational gradient in the Hengduan Mountains. (22nd July 2013) - Wu, Yongjie; Colwell, Robert K.; Rahbek, Carsten; Zhang, Chunlan; Quan, Qing; Wang, Changke; Lei, Fumin
Abstract: Aim: To document the species richness pattern of birds in the Hengduan Mountains and to understand its causes. Location: Hengduan Mountains, China. Methods: Species richness of 738 breeding bird species was calculated for each 100‐m elevational band along a gradient from 100 to 6000 m a.s.l. Climate data were compiled based on monthly records from 182 meteorological stations in the Hengduan Mountains from 1959 to 2004. We calculated the planimetric area, predicted richness under geometric constraints, three‐year average NDVI (normalized difference vegetation index) and EVI (enhanced vegetation index) in each elevational band. Simple and multiple regression models were used to test the explanatory power of variables associated with different factors proposed to account for elevational species richness gradients. Results: The elevational pattern in species richness, for all breeding birds, was hump‐shaped, with the peak occurring at 800–1800 m elevation. Endemic and non‐endemic species, as well as four elevational range size categories of birds, also showed the general hump‐shaped patterns of species richness, but with peaks at different elevations. In most data sets, species richness correlated well with climatic and energy factors along the elevational gradients; seasonality and productivity had a strong statistical relationship with species richness of montane birds in this study, with geometric constraints contributing to richness patterns for larger‐ranged species endemic to the gradient. Main conclusions: We found that climatic and energy factors correlate well with the richness pattern of birds, and that on the surveyed subtropical mountain, the elevational bands with highest seasonality harbour fewer species than areas with less seasonal variation in temperature. The results, however, vary somewhat among taxonomic groups. The most diverse species groups and species with the broadest ranges have a disproportionate influence on our perception of the overall diversity pattern and its underlying explanatory factors.